2004
DOI: 10.1161/01.cir.0000129225.67353.1f
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hyperglycemia Attenuates Coronary Collateral Development and Impairs Proliferative Properties of Myocardial Interstitial Fluid by Production of Angiostatin

Abstract: Background-Development of coronary collateral vessels is impaired in patients with diabetes mellitus. We tested the hypothesis that hyperglycemia alone attenuates collateral development and abolishes proliferative properties of myocardial interstitial fluid (MIF) by enhancing expression of matrix metalloproteinases (MMP) and angiostatin. Methods and Results-Chronically instrumented dogs were randomly assigned to receive an infusion of normal saline (control; nϭ9) or 70% dextrose in water to increase blood gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 24 publications
2
60
0
5
Order By: Relevance
“…Weirauch et al demonstrated reduced collateral-dependent perfusion in chronically instrumented dogs under hyperglycemic conditions and demonstrated the critical role of angiostatin in inhibiting collateral vessel formation in response to repetitive coronary occlusion, both in vivo and in vitro. 27 We have reproduced some of their findings in a clinically relevant model of diabetes and chronic myocardial ischemia by demonstrating a profound (Ͼ4-fold) increase in angiostatin expression in diabetic animals. In addition, diabetes was also associated with a 2-fold increase in endostatin expression.…”
Section: Controlmentioning
confidence: 54%
“…Weirauch et al demonstrated reduced collateral-dependent perfusion in chronically instrumented dogs under hyperglycemic conditions and demonstrated the critical role of angiostatin in inhibiting collateral vessel formation in response to repetitive coronary occlusion, both in vivo and in vitro. 27 We have reproduced some of their findings in a clinically relevant model of diabetes and chronic myocardial ischemia by demonstrating a profound (Ͼ4-fold) increase in angiostatin expression in diabetic animals. In addition, diabetes was also associated with a 2-fold increase in endostatin expression.…”
Section: Controlmentioning
confidence: 54%
“…[6][7][8] Many studies have indicated that inadequate angiogenic response to ischemia may result in severe organ damage attributable to poor collateral vessel formation and decreased new vessel formation. 9,10 The four and a half Lin11, Isl-1 and Mec-3 (LIM) domain (FHL) protein family is a newly identified group of proteins containing FHLs. This family consists of 6 members-FHL1, FHL2, FHL3, FHL4, FHL5, and activator of cAMP-responsive element modulator in testes.…”
mentioning
confidence: 99%
“…To test this hypothesis, the effects of high glucose treatment (46) [a condition mimicking diabetic conditions (62)] on endothelial function, O 2 •Ϫ and H 2 O 2 production, and inflammatory gene expression were compared in cultured arteries and cells of longerliving P. leucopus and shorter-living M. musculus.…”
mentioning
confidence: 99%